A literature review on the parvovirus B19 infection in sickle cell anemia and β-thalassemia patients - Soltani, Saber (Trop Med Health, 2020)
BACKGROUND: Parvovirus B19 is the causative agent for erythema infectiosum, and also as a potentially life-threatening infectious agent, it is mainly presented in high erythrocyte turnover patients. Sickle cell disease (SCD) is an inherited monogenic hematological disorder resulting from the mutations in the hemoglobin β-chain gene. Thalassemia is a hereditary hematological syndrome that happens in consequence of deficiencies in the production of one or more globin chains. We summarize current knowledge about the prevalence rates of the parvovirus B19 infection in sickle cell anemia and thalassemia patients. METHODS: Several online databases were searched including, Scopus, EMBASE, Web of Science, Google Scholar, and PubMed, which were performed amidst 2009–2019 by using distinct keywords: “Thalassemia,” “Parvovirus,” “Anemia,” “Sickle cell anemia,” “parvoviridae,” “parvoviridae infection,” and “parvovirus B19.” RESULTS: Search results indicated 4 and 7 studies for the prevalence of the parvovirus B19 in β-thalassemia and SCD, respectively. Among the β-thalassemia patients, the B19V seroprevalence for IgG and IgM were ranged from 18.2–81% and 14.5–41.1%, respectively; meanwhile, B19V DNA positively results was 4–15.3%. Moreover, in the SCD group, the extent of B19V IgG was varied from 37.6 to 65.9% and that of IgM was in a range of 2.9–30%, and the DNA detection rate was 4–54%. CONCLUSION: B19V seroprevalence changes in several conditions including, different epidemiological features, socio-economic status, and overpopulation. Age can expand the incidence of anti-B19V IgG/IgM in SCD and beta-thalassemia patients. Reinfection and diverse genotypes are relevant factors in the seroprevalence of B19v. The patients’ immunological-hematological station and higher abundance of transfusions can affect the B19V seroprevalence in SCD and beta-thalassemia group. Further investigations in this field could be suggested to better understand the virus distribution in this susceptible population of patients.